2006
DOI: 10.1055/s-2005-873050
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from Photosynthetic Characteristics for the Hybrid Origin of Diplotaxis muralis from a C3‐C4 Intermediate and a C3 Species

Abstract: Artificial hybridization studies have been carried out between plants with different photosynthetic types to study the genetic mechanism of photosynthetic types. However, there are only few reports describing the possibility of natural hybridization between plants with different photosynthetic types. A previous cytological and morphological study suggested that a cruciferous allotetraploid species, Diplotaxis muralis (L.) DC. (2n = 42), originated from natural hybridization between D. tenuifolia (L.) DC. (2n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…We found that the Γ value was highly and negatively correlated with the ratio of centripetally located chloroplasts in the BS cells and with the ratios (BS : M) of mitochondrial size and of labeling density of the GDC P-protein. It is also important to note that complete suppression of the expression of the GDC P-protein in the M cells is not required to reduce Γ, as revealed in our previous studies (Ueno et al, 2003(Ueno et al, , 2006b. Based on the data from the present study and our previous findings (Ueno et al, 2003), the C 3 -C 4 intermediate characteristics generally appear to be inherited in hybrid plants on the basis of the ratio of the parent genomes.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…We found that the Γ value was highly and negatively correlated with the ratio of centripetally located chloroplasts in the BS cells and with the ratios (BS : M) of mitochondrial size and of labeling density of the GDC P-protein. It is also important to note that complete suppression of the expression of the GDC P-protein in the M cells is not required to reduce Γ, as revealed in our previous studies (Ueno et al, 2003(Ueno et al, , 2006b. Based on the data from the present study and our previous findings (Ueno et al, 2003), the C 3 -C 4 intermediate characteristics generally appear to be inherited in hybrid plants on the basis of the ratio of the parent genomes.…”
mentioning
confidence: 56%
“…The antiserum was against the P-protein of GDC isolated from pea leaf mitochondria and was kindly provided by Dr. D. J. Oliver (University of Idaho, Moscow, ID, USA). This antiserum was the same as that used in our previous immunocytochemical studies (Ueno et al, 2003(Ueno et al, , 2006b). The density of labeling for GDC P-protein was determined by counting the gold particles on electron micrographs at 25000 × magnification and calculating the number per unit area (µ m -2 ).…”
Section: Anatomical and Ultrastructural Studiesmentioning
confidence: 99%
“…The amphidiploid (DtDtRR) had characteristics intermediate between the C 3 -C 4 intermediate (D. tenuifolia, DtDt) and C 3 (R. sativus, RR) parents, the sesquidiploid (DtDtR) had the characteristics close to the C 3 -C 4 intermediate parent and other sesquidiploid (DtRR) had strongly C 3 parent characteristics (Ueno et al, 2003). Such a mode of inheritance in the C 3 -C 4 intermediate and C 3 characteristics has also been demonstrated in the hybrids between Diplotaxis muralis (DtDtDvDv) and its ancestral species D. tenuifolia (DtDt) or D. viminea (DvDv), and in the reciprocal hybrids between M. arvensis and B. oleracea (C 3 ) with various genome constitutions (Ueno et al, 2006;. It is suggested that the constitution ratio of the C 3 -C 4 intermediate genome to the C 3 genome in their hybrids is the most important factor determining the degree of expression of the C 3 -C 4 intermediate characteristics.…”
Section: Discussionmentioning
confidence: 87%
“…However, the Γ of the auto-and alloplasmic DALs carrying one pair of 'b' M. arvensis chromosomes (RMa-b and MaR-b DALs) was significantly different from that of R. sativus (C 3 ), although that of the auto-and alloplasmic MALs with one 'b' M. arvensis chromosome was not signifi cantly different from that of R. sativus (C 3 ). As the amphidiploid showed a Γ intermediate between that of the C 3 -C 4 intermediate and C 3 parents (Ueno et al, 2003;2006;, the present two DALs (RMa-b and MaR-b DALs) also showed intermediate values. When the constitution ratio of the DALs was considered at the individual chromosome level, the constitution ratio of the C 3 -C 4 intermediate chromosome to the C 3 chromosome was 1:1 because they have one pair of homologous chromosomes of the C 3 -C 4 intermediate (M. arvensis) and the C 3 plant (R. sativus).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation